MUC1-C is necessary for SHP2 activation and BRAF inhibitor resistance in BRAF(V600E) mutant colorectal cancer. (10th April 2023) - Morimoto, Yoshihiro; Yamashita, Nami; Hirose, Haruka; Fushimi, Atsushi; Haratake, Naoki; Daimon, Tatsuaki; Bhattacharya, Atrayee; Ahmad, Rehan; Suzuki, Yozo; Takahashi, Hidekazu; Kufe, Donald W.
Abstract: Colorectal cancers (CRCs) harboring the BRAF(V600E) mutation are associated with aggressive disease and resistance to BRAF inhibitors by feedback activation of the receptor tyrosine kinase (RTK)→RAS→MAPK pathway. The oncogenic MUC1-C protein promotes progression of colitis to CRC; whereas there is no known involvement of MUC1-C in BRAF(V600E) CRCs. The present work demonstrates that MUC1 expression is significantly upregulated in BRAF(V600E) vs wild-type CRCs. We show that BRAF(V600E) CRC cells are dependent on MUC1-C for proliferation and BRAF inhibitor (BRAFi) resistance. Mechanistically, MUC1-C integrates induction of MYC in driving cell cycle progression with activation of the SHP2 phosphotyrosine phosphatase, which enhances RTK-mediated RAS→ERK signaling. We demonstrate that targeting MUC1-C genetically and pharmacologically suppresses (i) activation of MYC, (ii) induction of the NOTCH1 stemness factor, and (iii) the capacity for self-renewal. We also show that MUC1-C associates with SHP2 and is required for SHP2 activation in driving BRAFi-induced feedback of ERK signaling. In this way, targeting MUC1-C in BRAFi-resistant BRAF(V600E) CRC tumors inhibits growth and sensitizes to BRAF inhibition. These findings demonstrate that MUC1-C is a target for the treatment of BRAF(V600E) CRCs and for reversing their resistance to BRAF inhibitors by suppressing the feedback MAPK pathway. Highlights: MUC1 gene expression is upregulated in BRAF(V600E), as compared to wild-type (WT) BRAF, CRCs. The MUC1-C subunit is necessary for proliferation and BRAFi resistance of BRAF(V600E) CRC cells. MUC1-C is necessary for activation of SHP2 and induction of RTK→RAS→MAPK pathway in response to BRAF inhibition. Targeting MUC1-C inhibits BRAF(V600E) tumorigenicity and abrogates BRAFi resistance. MUC1-C is a target for the treatment of BRAF(V600E) CRCs and for reversing their resistance to BRAF inhibitors.